Predictive Analysis of Student Academic Performance Using Ensemble Learning Methods: A Case Study on the Portuguese Student Performance Dataset - Hakim, Mujibul; Zuliarso, Eri; Hidayat, Husni; Imam, Muhammad Nurul; Sholehudin, Mukti Ahmad (Fakultas Teknik Universitas Lambung Mangkurat, 2026)
The ability to predict student academic performance at an early stage is crucial for educational institutions to provide timely interventions. This research aims to apply and evaluate the effectiveness of ensemble learning methods in predicting the final grades (G3) of secondary school students using the UCI